ANALISIS KOMPOSISI MUSIK TERBANG JIDUR GRUP GAPURA SEJATI DESA JATI WETAN KECAMATAN JATI KABUPATEN KUDUS - PRASODJO, ANOM HASTO (Universitas Negeri Semarang, 2016)
The Result of this research shows that:(1) Polaritme found in all of musical instruments of Terbang Jidur played by Gapura Sejati Group and the musical pattern that judged by the differences of the musical instruments but they sounds very harmony (2) The melody used in song entitled Ã¢â‚¬Å“SolaÃ¢â‚¬Â and Ã¢â‚¬Å“TanaqolÃ¢â‚¬Â all of them using vocal melody, in this case means that there are no instruments played as a melody instrument which used by Gapura Sejati Group.(3) Ã¢â‚¬Å“SolaÃ¢â‚¬Â song has 3 parts, A-B-C, which are A Ã¢â‚¬â€œ B Ã¢â‚¬â€œ B Ã¢â‚¬â€œ C Ã¢â‚¬â€œ C. Ã¢â‚¬Å“SolaÃ¢â‚¬Â has a sequence A(a,x), B (b,y), C (c,z). While Ã¢â‚¬Å“TanaqolÃ¢â‚¬Â song has 4 parts, A-B-C-D, which are A Ã¢â‚¬â€œ B Ã¢â‚¬â€œ B Ã¢â‚¬â€œ C Ã¢â‚¬â€œ C Ã¢â‚¬â€œ D - D. In Ã¢â‚¬Å“TanaqolÃ¢â‚¬Â song has a sequence like this A(a,x), B (b,y), BÃ¢â‚¬â„¢ (bÃ¢â‚¬â„¢,yÃ¢â‚¬â„¢), C (c,z), C (c,z), CÃ¢â‚¬â„¢(cÃ¢â‚¬â„¢,zÃ¢â‚¬â„¢), D (d,xx), DÃ¢â‚¬â„¢ (d,xx). (4) The Rhymes in Ã¢â‚¬Å“SolaÃ¢â‚¬Â dan Ã¢â‚¬Å“TanaqolÃ¢â‚¬Â using arabic language and tells us the story about prophet Muhammad SAW. The Tempo that played by both songs using fast tempo/pace, which has the purpose of joining the dakwah/syiar about islamic religion (5)The Dynamic of both songs can be recoqnized when there is a repetition, and the tempo become faster. Based on the analysis research of the musical composition of Terbang Jidur by Gapura Sejati Group, the writer suggests to get more variation and new rhytm patterns in the playability of Terbang Jidur. In addition of patterns can be as: (1) To get more creativity of the players in musicalization skills (2) By a new companion or new concept of musical lines can be a new thing and it can become a challenge for the players itself.